Incidence vrozených srdecních vad v Ceské republice--aktuální data - Sípek, A; Gregor, V; Sípek, A; Hudáková, J; Horácek, J; Klaschka, J; Skibová, J; Langhammer, P; Petrzílková, L; Klímová, B; Perinová, B; Wiesnerová, J (Ceska gynekologie, 2010)
AIM OF STUDY: An analysis of incidence of congenital heart defects (CHD) in the Czech Republic in the 1994 - 2008 period. An assessment of absolute numbers, frequencies and incidences for particular selected diagnoses according to 10th decennial revision of International Classification of Diseases (ICD-10). An analysis of pre- and postnatal incidences of selected diagnoses and of a secondary prevention measures efficiency in the Czech Republic. TYPE OF STUDY: A retrospective epidemiological analysis of congenital anomalies from the database of the National Register of Birth Defects (NRBD) of the Czech Republic. MATERIAL AND METHODS: Data from the NRBD from the 1994 - 2008 period were used. In our study, CHD incidences (ICD-10 Q20-Q28 Congenital malformations of the circulatory system group) in the Czech Republic were analyzed. First, CHD incidences in births were assessed - absolute numbers, frequencies and incidences for particular selected diagnoses. Second, absolute numbers, frequencies and incidences of particular selected diagnoses in prenatally diagnosed fetuses and a secondary prevention measures efficiency in selected CHD were evaluated. In a third part, survival of babies with CHD during the first year of their life was analyzed. RESULTS: In the period under the study, there were a total of 1 472 610 life births in the Czech Republic. Congenital malformations of the circulatory system (Q20-Q28) present more than 40% of all registered congenital anomalies and are themselves the most frequent birth defect group in births in the Czech Republic. As a whole, 29 133 CHD were diagnosed (197.83 per 10 000 live births) in 18 811 children (127.53 per 10 000 live births) in this period, which presents more than 36% of children born with a congenital anomaly in the Czech Republic during 1994 - 2008. CHD most frequently diagnosed in births were congenital malformations of cardiac septa (total 16 428, 145.05 per 10 000 live births, more than 55% of all CHD) and congenital malformations of great arteries (total 5389, 47.58 per 10 000 live births, more than 18% of all CHD). Further, prenatally diagnosed CHD were analyzed. Incidences for particular diagnoses as well as percentage of pregnancy termination were assessed. A rate of prenatally diagnosed was 11.35% in discordant ventriculoarterial connection (Q20.3), 8.35% in discordant atrioventricular connection (Q20.5), 49.41% in hypoplastic left heart syndrome (Q23.4), 7.64% in coarctation of aorta (Q25.1) and 9.71% in tetralogy of Fallot (Q21.3). These anomalies were parts of chromosomal syndromes in 42.58% and non-chromosomal syndromes in 9.33%. There were also associated malformations (from other systems than circulatory one). The most frequent were congenital malformations of the nervous system (Q00-Q07) - 14.59%, congenital malformations and deformations of the musculoskeletal system (Q65-Q79) - 12.44%, cleft lip and cleft palate (Q35-Q37) - 7.42% and congenital malformations of the urinary system (Q60-Q64) - 6.70%. In children born with a CHD, 84.53% were associated with other anomaly, out of which more than 70% were CHD only. Only about 14% were associated with anomalies from other (non-circulatory system) groups. Perinatal mortality was highest in hypoplastic left heart syndrome (Q23.4) - 327.103 per thousand and in tetralogy of Fallot (Q21.3) - 6.565 per thousand. CONCLUSIONS: The study presents current results of analysis of CHD incidences in the Czech Republic in the 1994 - 2008 period. Children born with a CHD make more than 36% out of all children born with a congenital anomaly. CHD themselves represents an important part (more than 40%) of all diagnosed congenital anomalies in the Czech Republic. Over the period of the study there was a slight increase of diagnosed CHD during 1994 - 1999 followed by a slight decrease from 2000 with an exception of 2007 year. The most frequent of diagnosed CHD were ventricular septal defect (Q21.0) and atrial septal defect (Q21.1). Both defects incidences changes influence not only a total CHD but also a total congenital anomalies incidence. An influence of prenatal diagnostics among the five selected CHD was most important in hypoplastic left heart syndrome (Q23.4), less so in others. In prenatal diagnostics group, it is necessary to distinguish between those anomalies, which led to pregnancy termination (parts of both chromosomal and non-chromosomal syndromes and/or association with other severe anomalies) and those in which pregnancy leads to a delivery (late diagnostics, operabile defects, parental decision). CHD can be a part of chromosomal syndromes. In our study, in prenatally diagnosed CHD it was more than 42%. A presence of other associated diagnoses of congenital anomalies in births will significantly influence infant mortality and morbidity.
Keywords: novorozenec; Infant, Newborn; Female; těhotenství; Pregnancy; Humans; ženské pohlaví; Česká republika; lidé; incidence; Incidence; vrozené srdeční vady; Czech Republic; Heart Defects, Congenital